Effecting of Ribosomal-Inactivating Proteins on Gene Expression of Cdr2 Gene in Pathogenic Candida Albicans Isolates - Muwafaq Mehdi, Yasser; Rasheed, Hadi Rahman; Majead Abed, Rabab; Mohammed Sadeq, Ali (ASJ - Academic Science Journal, 2024)
Twenty isolates of Candida albicans were collected, during the study period from December / 2020 to February / 2021. For a group of 20 married women suffering from vaginal infections in Baqubah city. All the isolates were multidrug resistance against 5 antifungals from different groups according to the susceptibility test. The result of minimum inhibition concentration (MIC) for antifungal (fluconazole) values were between (256-64) µg/ml and MIC values for ribosomal inactivating proteins, between 325–5200 µg/ml . Conventional PCR technique was used to detect the CDR2 gene that is a molecular marker of a functional resistance for azoles antifungals group, the results inducted the presence of CDR2 gene 100%, it presented in the 20 isolates. By using Real-time PCR technique the CDR2 gene gave a low expression after treatment (32)µg/ml with sub MIC concentration of fluconazole with average folding 0.1once and after treatment 325 µg/ml with sub MIC ribosomal inactivating proteins concentration again of compared with control with average folding 0.6 in different degrees in two isolates were multi-resistant to antifungals.